The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.addbeh.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Get with the program: Adherence to a smartphone app for smoking cessation

Abstract: Introduction Although engagement is generally predictive of positive outcomes in technology-based behavioral change interventions, engagement measures remain largely atheoretical and lack treatment-specificity. This study examines the extent to which adherence measures based on the underlying behavioral change theory of an Acceptance and Commitment Therapy (ACT) app for smoking cessation predict smoking outcomes, and user characteristics associated with adherence. Methods Study sample was adult daily smokers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(50 citation statements)
references
References 37 publications
(45 reference statements)
2
46
0
Order By: Relevance
“…Two studies included were a post-hoc analysis of the single arm pilot randomised control trials 31,32 . Three studies did not have a control group 29,33,34 .…”
Section: Design Features Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies included were a post-hoc analysis of the single arm pilot randomised control trials 31,32 . Three studies did not have a control group 29,33,34 .…”
Section: Design Features Of the Studiesmentioning
confidence: 99%
“…Six studies adopted automated data extraction from the application. Four studies 30,31,33,34,36 included automated motivational messages while another included a specific daily educational module on smoking cessation . Most studies have adopted a quit plan, pictorial and audio-visual, cost saving, coping skills, and social support features in the application for smoking cessation.…”
Section: Mobile Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have concluded that smartphone applications can be beneficial in monitoring and evaluating patients [23][24][25], as well as increasing adherence to medical interventions [26,27]. The BUS approach offers the ability to take these studies further in understanding real-time use and overall time spent on apps as a factor that could contribute to health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pilot studies have been utilized to evaluate a variety of mHealth technologies, including a pilot study to assess the usability and acceptability of a smartphone app ("MindSurf") designed to promote contentment, wellbeing, and goal achievement (Carey, Haviland, Tai, Vanags, & Mansell, 2016), adherence to a smartphone app for smoking cessation (Zeng, Heffner, Copeland, Mull, & Bricker, 2016), and using a smartphone app to promote psychiatric and physical well-being (Macias et al, 2015), among others. The overall rationale is that unlike the more established treatment protocols, delivered in more traditional settings, many mHealth-related technologies are often relatively new to the market and are by their very nature delivered in less traditional formats.…”
Section: Mhealth Technologiesmentioning
confidence: 99%